Pemanfaatan Karbon dari Sabut Buah Nipah (Nypa fruticans) untuk Penjernihan Minyak Jelantah - Istiqamah, Siti Sarah; Mawardi, Mawardi; Khair, Miftahul; Rahmi, Maulidia Arsyta; Novela, Riana; Pernadi, Niza Lian; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2024)
Along with the increase in the food and household industries, demand for raw materials for cooking oil continues to increase, causing shortages and increasing prices of cooking oil. This causes cooking oil to be used repeatedly. Cooking oil that has been used repeatedly is called used cooking oil which contains many carcinogenic compounds that can be harmful to health. Therefore, this research aims to purify used cooking oil using palm fiber carbon to improve the quality of used cooking oil. Nipa palm fiber contains hemicellulose and cellulose so it has the potential to be used as a carbon source using the calcination method and carrying out proximate tests such as ash content, vapor content and bound carbon content. Next, it is applied in the process of purifying used cooking oil using the adsorption method. After that, several properties of used cooking oil were tested, such as density, flow rate, acid number and saponification number. The results obtained in this research for the proximate test of palm fruit fiber at a temperature of 250-400℃ have met the SNI 06-3730-2021 standard. Nypa palm fiber carbon in used cooking oil was proven to reduce the density value to 0.81 g/mL, flow rate 4.17 mL/s, acid number 3.6 mg/KOH and saponification value 427 mg/KOH.